Features of The Hanzi Character ç¦ - Putri, Asyifa Rahmadhani Arief; Anastasya, Citrani Wafa (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
This research was inspirated by the author's curiosity about the specialty of Hanzi fÃº (ç¦) characters. This study aims to identify the meaning and specialty of Hanzi fÃº (ç¦) characters for Chinese people. The data collection technique used by the author is library research method. The method used by the author is descriptive qualitative method by describing the meaning of the fÃº (ç¦) character and obtaining data sources from journals and articles relevant to this research. This hereditary custom is usually affixed to the front doors, windows, and front walls of Chinese homes to welcome the Chinese New Year. The word fÃº (ç¦) is usually found in the spring of Chinese New Year. Each character that makes up the Chinese characters has a symbolic meaning that can represent human expressions and feelings. FÃº dÃ ole (ç¦åˆ°äº†) has the linguistic meaning of 'luck arrives', the pronunciation of FÃº dÃ ole (ç¦åˆ°äº†) is similar to the pronunciation of FÃº dÃ ole (ç¦å€’äº†) which means 'luck falls'. The benefit of this study is to provide knowledge to readers about the specialty of fÃº (ç¦) character for Chinese people. The result of this study can be known the meaning and tradition of Chinese people towards fÃº (ç¦) character.